Effects of dexmedetomidine on delirium and mortality during sedation in ICU patients: a systematic review and meta-analysis protocol. Issue 4 (3rd April 2019) - Sun, Rao; Wang, Shuo; Li, Shiyong; Yang, Chun; Zhao, Yilin; Luo, Ailin
Abstract : Introduction: Delirium is very common in patients admitted to intensive care unit (ICU), and may worsen survival in these patients. Several meta-analyses have evaluated the antidelirium effects of dexmedetomidine in ICU patients, but their findings were inconsistent. Recently, several large multicentre randomised clinical trials (RCTs) were published, but they have not yet to be included in any meta-analysis. We will conduct a meta-analysis adding these data to evaluate the effects of dexmedetomidine on delirium and mortality in ICU patients, aiming to terminate controversy and provide robust evidence for guiding clinical practice. Methods and analysis: The Cochrane Central Register of Controlled Trials, PubMed, Embase, ISI Web of Science will be searched from inception to 31 December 2018 for relevant RCTs. Two reviewers will independently screen the identified citations. After quality appraisal and data extraction of included studies, we will conduct meta-analyses for outcomes of interest, including delirium, mortality, length of ICU/hospital stay, time to extubation, ICU costs and adverse effects. The statistical heterogeneity among studies will be assessed by the χ 2 test and quantified by the I 2 statistics. We will undertake subgroup analyses to explore heterogeneity and sensitivity analyses to evaluate whether the results are robust. Potential publication bias will be assessed by funnel plot and Egger's test. At last, the quality of evidence of the main outcomes will be rated using the Grading of Recommendations Assessment, Development and Evaluation system. Ethics and dissemination: The present study is a meta-analysis based on published studies, thus ethical approval is not needed. Our review will elucidate whether dexmedetomidine could decrease the incidence of delirium and improve survival in ICU patients. Our findings may help clinicians to choose optimal sedative agents for ICU patients. The results of this meta-analysis will be submitted to a peer reviewed journal for publication. PROSPERO registration number: CRD42018095358.